Serum NLR combined with CA125 and HE4 improves the diagnostic and prognostic efficiency in patients with ovarian cancer - Tian, Yun; Li, Xiabing; Zhang, Hongjian; Wang, Yaping; Li, Hongyu; Qin, Qiaohong (Frontiers in Oncology, 2024)
BackgroundOvarian cancer (OC) represents a common neoplasm within the female reproductive tract. The prognosis for patients diagnosed at advanced stages is unfavorable, primarily attributable to the absence of reliable screening markers for early detection. An elevated neutrophil-to-lymphocyte ratio (NLR) serves as an indicator of host inflammatory response and has been linked to poorer overall survival (OS) across various cancer types; however, its examination in OC remains limited. This study seeks to identify combination diagnostic and prognostic markers for OC, aiming to improve diagnostic and prognostic efficacy, especially in the early stages.MethodsWe analyzed the targeted biomarkers in a cohort of 104 OC patients and 100 controls, which comprised 50 patients with benign ovarian tumors and 50 healthy women, using enzyme-linked immunosorbent assay (ELISA) and complete blood counting (CBC). After validating the biomarker panel, we compared the expression levels of the biomarkers in OC patients with various clinical features to assess their relevance. A biomarker panel was developed and validated with an independent cohort of 70 OC patients and 60 controls, including 30 with benign ovarian tumors and 30 healthy women. We evaluated the diagnostic accuracy using the area under the receiver-operating characteristic (ROC) curve and overall survival analysis was used for prognosis.ResultsThe results from ELISA and CBC analyses indicated that the NLR was significantly higher in patients with OC. This elevation was especially notable in those with advanced stages of the disease, lymph node metastasis, and ascites. The diagnostic performance of the NLR, when combined with CA125 and HE4, outperformed each marker used individually, especially when compared to the traditional combination of CA125 and HE4. Importantly, we observed similar results in patients with early-stage ovarian cancer and those with low levels of CA125 and HE4. In addition, these results suggest that NLR combined with CA125 and HE4 levels in OC patients have significant prognostic value.ConclusionsThe effective combination of serum NLR, CA125, and HE4 significantly enhances diagnostic efficiency in patients with OC. Serum NLR, CA125, and HE4 levels were identified as independent prognostic markers for OC.